Northern Textiles Limited (b) - Varma, J. R. (Jayanth R.); Ghosh, Rahul (London : Indian Institute of Management, Ahmedabad, 2024)
NTL suffered huge losses in its foreign exchange hedging activities as its highly complex leveraged structured products backfired badly in the wake of the Global Financial Crisis of 2007 and 2008. The CFO and the Treasury head have both been sacked, and Joshi, the new CFO, has embraced aggressive litigation as NTL’s survival strategy to cope with the losses that threaten its solvency. In the meantime, NTL also faces tax investigations and whistleblower allegations of fraud, and it finds that the record-keeping of its derivative transactions was hopelessly incomplete and patchy. A complete reconstruction of the entire derivative transaction history is the only way to rebuild trust, and that task falls on Reddy, a seasoned derivatives expert brought in by the Board specifically for this purpose. In this dire situation, Seth, the founder Chairman of NTL decides that NTL needs to put all this behind it and focus on rebuilding the business. The challenge for Seth, Joshi and Reddy is to go about doing this in an environment that offers very few rays of hope.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Textile industry -- Case studies; Hedging (Finance) -- Case studies